Effects of flower essences on nursing students’ stress symptoms: a randomized clinical trial* - Albuquerque, Lucia Maria Nunes Freire de; Turrini, Ruth Natalia Teresa (Revista da Escola de Enfermagem da USP, 2022)
Objective: To analyze the effects of flower essence bouquets on the signs and symptoms of stress in nursing students. Method: Randomized clinical trial, triple blind, with two groups, flower essence group and placebo group, carried out with 101 nursing students. The groups used the formula for 60 days at a dosage of 4 drops 4 times a day. The outcome was evaluated using the Baccaro Test and the Perceived Stress Scale applied at the beginning and at the end of the intervention. The outcome analysis was performed using the mixed effects model, with 〈 = 5% and the effect size verified by the Cohen’s d test. Results: There was no significant difference between the groups in stress reduction (p > 0.05). Both groups showed a reduction in scale scores (p < 0.001) with large effect size. There was an influence of the COVID-19 pandemic in the reduction of Baccaro Test scores. Conclusion: The intervention with flower essence therapy was not more effective than placebo in reducing stress signs and symptoms. Brazilian Registry of Clinical Trials: UTN U1111–1257-5715.